2004
DOI: 10.1007/s00442-004-1605-4
|View full text |Cite
|
Sign up to set email alerts
|

Cold and heat tolerance of drosophilid flies with reference to their latitudinal distributions

Abstract: The relation between thermal tolerance and latitudinal distribution was studied with 30 drosophilid species collected from the cool-temperate region (Sapporo), the warm-temperate region (Tokyo and Kyoto) and the subtropical region (Iriomote island) in Japan. In addition, intraspecific variation was examined for five species collected from two localities. The subtropical strains of Scaptodrosophila coracina, Drosophila bizonata and D. daruma were less tolerant to cold than their temperate strains. However, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
240
3
4

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 238 publications
(275 citation statements)
references
References 46 publications
17
240
3
4
Order By: Relevance
“…However, others have observed similar results for this species. In a study of the temperature tolerance of several Drosophilids sampled across latitudinal gradients in Japan, Kimura (2004) found that several species showed intraspecific differences in thermal tolerance depending on geographical origin. However, in the case of D. suzukii, Kimura found no difference in tolerance between cool-temperate and warm-temperate geographical strains.…”
Section: Discussionmentioning
confidence: 99%
“…However, others have observed similar results for this species. In a study of the temperature tolerance of several Drosophilids sampled across latitudinal gradients in Japan, Kimura (2004) found that several species showed intraspecific differences in thermal tolerance depending on geographical origin. However, in the case of D. suzukii, Kimura found no difference in tolerance between cool-temperate and warm-temperate geographical strains.…”
Section: Discussionmentioning
confidence: 99%
“…Although a more pronounced acclimation effect on lower than on upper limits is not universal [e.g. the converse has been found the caterpillars of the moth Embryonopsis halticella (Klok and Chown, 1998)], it does seem to be typical of most ectotherms (Kingsolver and Huey, 1998 Metabolic rate difference (ml CO 2 h -1 ) * * geographic variation in thermal limits, and in the responses of these limits to selection (Addo-Bediako et al, 2000;Chen et al, 1990;Chown, 2001;Gaston and Chown, 1999;Gilchrist et al, 1997;Hercus et al, 2000;Hoffmann et al, 1997;Kimura, 2004;Stanley et al, 1980;Terblanche et al, 2005b). Increases in metabolic rate of the G. pallidipes adults with adult exposure to low temperature seems to be typical of this group of tsetse flies because it has also been found in Glossina morsitans.…”
Section: Discussionmentioning
confidence: 99%
“…The range of drosophilids is limited by cold tolerance. In an effort to predict the ability of selected drosophilid species to expand their geographic ranges, Kimura ( 2004 ) (Lethal Temperature) of northern and southern strains of several species. There was little difference in northern and southern representative strains of SWD.…”
Section: Biologymentioning
confidence: 99%
“…However, this study used non-adapted, non-diapausing individuals for testing, and their conclusions may be conservative. Although a congeneric species, D. lutescens Okada, cannot tolerate winter conditions in Sapporo, Japan, it is common in this region in summer and autumn (Kimura 2004 ) . This period is the most problematic for SWD management in vineyards.…”
Section: Biologymentioning
confidence: 99%